Optimizing the spectral absorption profile of sunscreens. (25th July 2016) - Diffey, B. L.
Abstract: Objective: To investigate whether sunscreens provide optimal protection by exhibiting a uniform spectral absorption profile throughout the ultraviolet spectrum or by having a spectral profile in which absorption in the UVB waveband is greater than in the UVA region. Methods: A sunscreen with a flat spectral absorption profile was compared with one of the same SPF in which the SPF to UVA protection was in the ratio of 3 : 1 in terms of protecting against erythema and chronic effects with different action spectra, as well as the total UV burden to the skin. Results: A sunscreen with spectral profile in which absorption in the UVB waveband is greater than in the UVA region confers no benefit in terms of erythema (and endpoints with similar action spectra) than a sunscreen with the same SPF that exhibits uniform absorption at all wavelengths throughout the UV spectrum. More importantly, the '3 : 1 profile' offers inferior protection when endpoints with other action spectra are considered, as well as resulting in a total UV burden to the skin that is about 5 times higher than sunscreen products showing a flat spectral absorption profile. Conclusion: It may be tempting to believe that it is beneficial to increase the absorption of sunscreens in the UVB region relative to the UVA to reflect the fact that skin damage is associated more with UVB than UVA exposure. However, this belief is a fallacy and consumers are best served with sunscreens in which the spectral protection profile is uniform at all wavelengths throughout the UV spectrum. Abstract : Being clear about what is the ideal spectral absorption profile that sunscreens should aspire to is important not only to manufacturers and formulators in the design of new products, but also to consumers who need to make an informed choice about available products. This commentary discusses two candidate profiles; one based on greater absorption in the UVB waveband than in the UVA and the other showing equal absorption across all terrestrial UV wavelengths. Résumé: Objectif: Le but de l'étude était d'examiner si les écrans solaires offrent une protection optimale en présentant un profil d'absorption spectrale uniforme sur l'ensemble du spectre ultraviolet ou en ayant un profil spectral dans lequel l'absorption dans la bande d'ondes UVB est plus grande que dans la région des UVA. Méthodes: Un écran solaire avec un profil d'absorption spectrale plat a été comparé à un autre du même SPF dans lequel le rapport entre SPF et à la protection UVA était dans 3: 1, en termes de protection contre l'érythème et des effets chroniques avec des spectres d'action différents, ainsi que la charge totale aux UV sur la peau. Résultats: Un écran solaire avec profil spectral dans lequel l'absorption dans la gamme de longueur d'ondes UVB est plus grande que dans la région des UVA ne confère aucun avantage en termes d'érythème (et d'autres paramètres avec les spectres d'action similaires) qu'un écran solaire avec le même SPF qui présente une absorption uniforme à toutes les longueurs d'onde dans tout le spectre UV. Plus important encore, le "profil 3: 1″ offre une protection inférieure lorsque les extrémités avec d'autres spectres d'action sont considérées, ainsi que résultant en une charge totale aux UV sur la peau qui est environ 5 fois plus élevé qu'avec les produits de protection solaire montrant un profil d'absorption spectrale plat. Conclusion: Il peut être tentant de croire qu'il soit bénéfique d'augmenter l'absorption des écrans solaires dans la région UVB par rapport à l'UVA pour refléter le fait que les dommages de la peau sont associés plus avec UVB qu'avec l'exposition UVA. Cependant, cette croyance est une erreur et les consommateurs sont mieux servis avec des écrans solaires dans lequel le profil de protection spectrale est uniforme à toutes les longueurs d'onde à travers le spectre UV.